Antiobesity activity of bambu tali (Gigantochloa apus (Schult.) Kurz) leaves tea in wistar rats - Desi Ambarwati; Sapto Yuliani; Arsyannur Pratiwi (Pharmaciana, 2020)
Obesity is an increase in body weight that exceeds normal and the risk of serious illness. Bambu Tali leaves (Gigantochloa apus (Schult.) Kurz) contain flavonoids, tannins, and saponins, which can inhibit the absorption of fatty acids in the digestive tract and excrete them through feces to lose weight. This study examines the tea activity of the Bambu Tali leaves in inhibiting weight gain, total cholesterol, and triglyceride levels of obese Wistar rats fed with a high-fat diet (HFD). A total of 30 Wistar rats were divided into 6 groups: normal control (standard feed), negative control (HFD), positive control (HFD + Orlistat), and 3 groups of tea doses of Bambu Tali leaves (HFD + 360, HFD + 720, HFD + 1440 mg/kg BW). HFD was given together with the Bambu Tali leaf tea for 35 days. On the 36th day, the blood sample was taken to measure cholesterol and triglyceride levels. The weighing was conducted weekly. The results showed that giving HFDincreased body weight significantly, total cholesterol, and triglyceride levels (p <0.05). Bambu Tali leaf tea at doses of 720 and 1440 mg/kg BW could significantly inhibit weight gain (p <0.05). Bambu Tali leaf tea with doses of 360, 720, and 1440 mg/kg BW can also inhibit the increase in total cholesterol levels (p<0.05). Meanwhile, the inhibition of a significant increase in triglyceride levels (p <0.05) only occurs at a dose of 1440 mg/kg BW. This study concludes that Bambu Tali leaf tea has antiobesity activity by inhibiting weight gain, total cholesterol levels, and plasma triglycerides of Wistar rats.